Metodología del entrenamiento y su incidencia en la preparación técnica en los estudiantes de la selección de futbol de varones de la Unidad Educativa Ricaurte - Flor Vera, Walter Javier (2017)
The Final Research Report with the theme: "The methodology of training and its impact on the technical preparation of students of the soccer team of the Ricaurte Educational Unit in the period 2017", reveals the current situation presented by football coaches of the aforementioned institution, in order to comply with the foreseen objectives, methods were selected from the theoretical and empirical levels of scientific research, using mathematical and statistical methods in order to process and validate the results obtained. The shortcomings appreciated in the visits made to ten training sessions served as the basis for determining the elements that a Model must contain to sustain the training system for the development of the technical condition of student athletes of the Ricaurte Educational Unit, which they travel through the school categories. We think that the use of the proposed elements, as a basis for the elaboration of the aforementioned model, can contribute to raising the scientific level of the coaches to face the pedagogical direction of the training process aimed at developing the technical capabilities of their athletes